Formation of tin-based crystals from a SnAgCu alloy under formic acid vapor. (7th November 2018) - Conti, Fosca; Hanss, Alexander; Mokhtari, Omid; Bhogaraju, Sri Krishna; Elger, Gordon
Abstract : A new method is developed to crystallize tin formates in a formic acid-enriched nitrogen atmosphere. The SAC alloy is used. Abstract : The use of formic acid vapor in soldering is growing. In the presence of SnAgCu powder, used as a bonding material to replace Pb-containing alloys, undesired deposits are observed. To understand this phenomenon, the mass change of a sample of alloys was investigated between 40 and 260 °C and the evolved gas was analyzed. In the quest to identify the unwanted deposits, a new strategy was researched and developed to increase the quantity of the produced deposit and to obtain it on a target surface for further studies. Unexpectedly, crystals were produced. The growth process of the crystals was optimized to reach crystal structures at nearly 1 mm in height. Unusual shapes were detected.